Peningkatan Perkembangan Kognitif Anak Usia Dini Melalui Media Bermain Memancing - Retnaningrum, Wulandari (STAIT Yogyakarta, 2018)
This study aims to know the process and result of the lesson toimprove cognitive development through fishing games for group B children ofkindergarten Miftahul Huda Cilacap District.This research was a kind ofclassroom action research.This study used the Kemmis and Taggart’sdesign.Each cycle consists of four phases: planning, action, observation, andreflection. The research subjects are group B children of Kindergarten MiftahulHuda. The data collection techniques included observation, interviews, anddocumentation study. The collected data were analyzed using descriptivequalitative and quantitative methods. The results of the study show that thecognitive development of child before the action is still in the category ofbeginning to developing, that is 58,55%; the results first cycle reaches69,62%in the category of developing and the second cyclereaches 80,99% in a categoryof highly developed; the use of fishing games has a very good impact oncognitive development shown by the cognitive development of the children,which is higher after the action compared to that before the action.